Literature Review: Pengelolaan Manajemen Logistik Dalam Pengadaan Obat Di Rumah Sakit Di Jabodetabek - Siti Humaira Syarif; Adjrina Dawina Putri; Tania Rahmayanti; Risma Pertiwi; Kazhima Alma Azzahra; Rossa Shafira Nur Sabrina; Putri Andini Novianti; Acim Heri Iswanto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2023)
The background of this Literature Review is based on stagnant events and stockouts of certain drugs at health care facilities in Jabodetabek which have had a detrimental impact on the location concerned. This study is used to analyze the management of drug logistics management in health care facilities in Jabodetabek. The Literature Review method uses 7 article sources from Google Scholar using the keywords drug procurement, logistics management, and hospital. The results obtained were that in several research locations there were several problems such as drug reserves, drug distribution, to the withdrawal and destruction of drugs which were directly related to the implementation of logistics management. The conclusion that can be drawn is that the management of logistics management of medicines in health care facilities in Jabodetabek is one of the conditions that must be carried out by every health service and is useful in providing good quality health services. If logistics management is carried out properly, this can increase the effectiveness and efficiency of services in health facilities and special attention is needed from various sectors to carry out logistics management of medicines in health care facilities according to existing standards.